Coaching to support apprentice’s ability to manage their own (further) competence development: results of a case study and their implications - Keller, Anna [Verfasser]; Barabasch, Antje [Verfasser] (My University, 2022)
“In vocational education and training, coaching can be used to support apprentices’ ability to manage their own (further) competence development ‘on the job’. This is largely requested among employees at workplaces in internationally competitive sectors of the economy which require of their workforce a great deal of flexibility and learning ability. So far, little is known about coaching practices in vocational education and training. The aim of this paper is to explore how coaching is used in vocational training in a large Swiss enterprise of the communication- and IT- services sector. The for this purpose analysed case study data comprises 30 interviews with apprentices, workplace trainers, coaches, and members of VET management of the enterprise, protocols of site visits and an analysis of VET related documents. As also VET schools must train learners for the contemporary world of work and must foster their ability to increasingly manage their own (further) competence development, coaching could be an interesting approach to be used in VET schools. This is critically discussed in the second part of the paper, respecting the different conditions that apply for supporting learning at the workplace- and supporting learning in the VET school context.” (authors’ abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 3.2.2 Großunternehmen; 370; Berufsausbildung; Coaching; Kompetenzentwicklung; Großunternehmen; Informationswirtschaft; Befragung; Berufsschule; Schweiz